THE INFLUENCE OF FEMALE LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND WORK MOTIVATION ON EMPLOYEE DISCIPLINE AT THE FINANCE AND ASSET BUREAU, SECRETARIAT GENERAL, MINISTRY OF HOME AFFAIRS - Humairo, Haliza; Affini, Dinar Nur; Darlion, Freska Lionia (International Humanities and Applied Science Journal, 2025)
Abstract – This research examines the impact of female leadership styles, organizational culture, and work motivation on employee discipline within the Finance and Asset Bureau of the Secretariat General of the Ministry of Home Affairs. The study involves two types of variables: the dependent variable (Employee Discipline) and the independent variables (Female Leadership Style, Organizational Culture, and Work Motivation). The research population consists of all 73 employees at the Finance and Asset Bureau, with the entire population serving as the sample (saturated sampling). Data were collected using quantitative methods, including questionnaires and literature reviews. The data were analyzed descriptively and through Structural Equation Modeling Partial Least Square (SEM-PLS) using SmartPLS 4.0, incorporating validity and reliability tests. Findings indicate that Female Leadership Style, Organizational Culture, and Work Motivation each have a positive and significant influence on Employee Discipline at the Finance and Asset Bureau of the Secretariat General of the Ministry of Home Affairs. Keywords: Employee Discipline; Female Leadership Style; Organizational Culture; Work Motivation